106 Are referrals for non-invasive ventilations (niv) in patients with motor neurone disease (mnd) processed in a short time?. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Shanmugalingam, Thurkaa; Roebuck, Harriet
Abstract : Background: Patients with MND are at risk of respiratory compromise due to chest wall weakness and require NIV. As prognosis is short this should be a rapid referral to respiratory services. We advise that time between referral and assessment should be aimed at <6 weeks. Methods: Neurorehabilitation team lead supplied the details of eight MND patients referred for NIV assessments to Colchester Hospital (CHUFT) within the last twelve months. The usual referral pathway is via Papworth Hospital Cambridge but these patients were either too unwell or had chosen not to travel to Cambridge for assessment. A review of the patient's paper notes, Order comms system, Electronic Discharge Summaries, Respiratory clinic letter database and the separate patient neurorehab notes was undertaken. Results: One patient has been managed by Basildon Hospital so excluded from the audit which focused on CHUFT services. Of the seven remaining patients, two have not been seen by respiratory services as yet and the reason is unclear. One patient was admitted to Colchester General Hospital with life threatening respiratory compromise two months after referral and started NIV therefore as an inpatient. The final four patients were seen at 13 days, 6 weeks and (2x) 4 months post referral. Conclusion: There is no standard best practice process for managing these referrals. The NICE quality standard does not advise the time by which these patients should be assessed by respiratory services post referral. The tests required also could be standardised. At present it is not clear whether they require an arterial blood gas or sleep study. It might also be possible to start NIV and assess symptomatic benefit without tests. Writing agreed local guidelines would therefore be beneficial. In light of the patients short prognosis with MND it might advisable to aim for review in <6 weeks.